S09-3 Evidence of the impact of Sport Policies on physical activity and sport participation: A Systematic Mixed Studies Review. (29th August 2022) - Volf, Kevin; Kelly, Liam; Bengoechea, Enrique García; Casey, Bláthín; Gelius, Peter; Messing, Sven; Forberger, Sarah; Lakerveld, Jeroen; Den Braver, Nicolette R; Zukowska, Joanna; Woods, Catherine; ,
Abstract: Background: Sport is recognised as a potential public health intervention through its influence on physical activity (PA) levels and consequent health benefits. International policy actors such as the Council of Europe, the World Health Organisation and the International Society for Physical Activity and Health have recommended that sport for all is promoted both for public health and as a basic right. Purpose: This review aims to provide evidence to support the development of policies aimed at maximising the opportunity to participate in PA and sporting activity. Methods: We systematically searched six electronic databases for quantitative, qualitative, and review studies investigating how public sport policy affects PA and sport participation outcomes". The scientific literature was screened according to predetermined eligibility criteria. Following study selection and data extraction, the quality was assessed using modified versions of existing quality assessment tools. Results were synthesised narratively. Results: Database searches identified 3705 unique articles. A total of 93 full-text articles were assessed, with 31 meeting our inclusion criteria. Fourteen unique policy actions were identified and were categorised into the policy areas Build Sport Facilities, Reduce Financial Barriers, Build Capacity and Establish Partnerships with Sport Sector, and Promote Public Interest in Sports. Conclusions: Policy actions to promote physical activity and sport participation have demonstrated qualified success but there is limited evidence of success in reaching hard to reach groups. Therefore, policymakers utilising sport to increase physical activity should treat it as a complementary intervention alongside other policy actions based on a systems perspective.